An atlas of impossible longing - Roy, Anuradha (Free Press, 2011)
"Roy's impressive American debut covers multiple generations of an Indian family from the turn of the 20th century to India's partition. Three distinct sections revolve around Amulya, who runs an herbal medicine and fragrance business; his mentally ill wife, Kananbala, who spies on the goings-on of her English neighbors from the room Amulya keeps her locked in; their sons, Kamal and Nirmal; their wives; Nirmal's daughter Bakul, whose mother died in childbirth; and finally Mukunda, an orphan that Amulya helps support, at which point Nirmal brings Mukunda home as a companion for Bakul. Tales weave backward and forward, and characters wallow in their longings, occasionally taking action; Mukunda and Bakul form a lasting bond that doesn't change with their circumstances. The book unfolds in third person until the final section, when Mukunda steps in as narrator to provide a welcome personal perspective on years of events. Roy is especially good at sensory description, making the sounds, smells, and feel of Bengal come vividly to life. Cultures may differ, but longing and love are universal." --Publishers weekly